2015
DOI: 10.2147/tcrm.s87761
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between eosinophilia and slow coronary flow

Abstract: AimThe pathophysiology of slow coronary flow (SCF) involves atherosclerosis, small vessel dysfunction, platelet function disorders, and inflammation. It has been known that eosinophils also play a significant role in inflammation, vasoconstriction, thrombosis, and endothelial dysfunction. We propose to evaluate the relationship between eosinophilia and SCF.MethodsAll patients who underwent coronary angiography between January 2011 and December 2013 were screened retrospectively. Of 6,832 patients, 102 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Both high monocyte, eosinophil, and neutrophil counts and a low lymphocyte count reflect systemic inflammation and physiologic stress and contribute to the development of cardiovascular disease. 2833…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both high monocyte, eosinophil, and neutrophil counts and a low lymphocyte count reflect systemic inflammation and physiologic stress and contribute to the development of cardiovascular disease. 2833…”
Section: Discussionmentioning
confidence: 99%
“…Both high monocyte, eosinophil, and neutrophil counts and a low lymphocyte count reflect systemic inflammation and physiologic stress and contribute to the development of cardiovascular disease. [28][29][30][31][32][33] The relationships between the LMR, ELR, and NLR and adverse events in patients with oncological and cardiac diseases have been revealed in several recent studies. The NLR, ELR, and LMR, which are easily calculated from the CBC count, have been shown to be potential diagnostic and prognostic indicators of some malignant subtypes and cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We read the article by Altas et al8 regarding the relationship between the eosinophil count and the CSFP with great interest. They showed that of the complete blood count components (white blood cells, neutrophils, eosinophils, hemoglobin, and platelets), eosinophils were associated with the CSFP.…”
mentioning
confidence: 99%
“…Clinical manifestations of these procoagulant and prothrombotic issues are well described in patients with peripheral eosinophilia such as hypereosinophilic syndromes [21,22]. Furthermore, relatively high peripheral EOS content has been found in patient with vasospastic angina, unstable angina pectoris, instent restenosis, coronary slow flow, and syndrome X [23][24][25][26][27]. After 20 years of follow-up, EOS level was significantly associated with increased risk of future cardiovascular events, and EOS cationic protein was defined as a new biomarker of coronary atherosclerosis [28].…”
Section: Discussionmentioning
confidence: 99%